2008
DOI: 10.1158/1078-0432.ccr-07-1593
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to Epidermal Growth Factor Receptor Inhibitor Requires E-Cadherin Expression in Urothelial Carcinoma Cells

Abstract: Purpose: Epidermal growth factor receptor (EGFR) is an attractive target for the treatment of urothelial carcinoma, but a clinical response can be expected in only a small proportion of patients. The aim of this study was to define molecular markers of response to cetuximab therapy in a panel of urothelial carcinoma cell lines. Experimental Design: Eleven cell lines were investigated for antiproliferative response to cetuximab based on [ 3 H]thymidine incorporation. A variety of markers, including EGFR express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
85
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 39 publications
6
85
0
Order By: Relevance
“…Specifically, the combined inhibition of PI3K/Akt and b-catenin signaling may block the transformed growth of such E-cadherindeficient cells. Recent studies have shown that E-cadherin-deficient tumors are more resistant to treatment with epidermal growth factor receptor inhibitors (Yauch et al, 2005;Witta et al, 2006;Black et al, 2008). One possible explanation is that specific epidermal growth factor receptor inhibitors may fail to inhibit the growth of E-cadherin-deficient cells because b-catenin signaling could still promote the constitutive activation of PI3K/Akt signaling by inhibition of PTEN expression, thus promoting transformed growth.…”
Section: Regulation Of Pten Levels By Cell Density and E-cadherin-cadmentioning
confidence: 99%
“…Specifically, the combined inhibition of PI3K/Akt and b-catenin signaling may block the transformed growth of such E-cadherindeficient cells. Recent studies have shown that E-cadherin-deficient tumors are more resistant to treatment with epidermal growth factor receptor inhibitors (Yauch et al, 2005;Witta et al, 2006;Black et al, 2008). One possible explanation is that specific epidermal growth factor receptor inhibitors may fail to inhibit the growth of E-cadherin-deficient cells because b-catenin signaling could still promote the constitutive activation of PI3K/Akt signaling by inhibition of PTEN expression, thus promoting transformed growth.…”
Section: Regulation Of Pten Levels By Cell Density and E-cadherin-cadmentioning
confidence: 99%
“…One potential mechanism underlying this observation is that high Tβ4 expression mainly accelerates the deteriorative process via specific EMTinducing signals in advanced BTCC, thereby inducing local invasion and distant metastasis; however, the precise details of how this process directly affects recurrence in early-stage carcinoma remains unknown. In addition, E-cadherin is not only the first and most important regulator of the EMT but also is clearly associated with the clinical outcomes of BTCC, such as recurrence [24]. However, several factors (e.g., microRNA-205, Twist) or pathways (e.g., epidermal growth factor receptor, tumor necrosis factor-related apoptosisinducing ligand) might interact with Tβ4 or influence the biological features of BTCC through acting on E-cadherin expression [25]; as a result, our findings demonstrated that Tβ4 was likely not an independent prognostic factor for recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups reported that sensitivity to EGFR directed therapy is associated with expression of E-cadherin and other characteristics of a typical "epithelial" tumor phenotype [35][36][37][38][39]. Loss of E-cadherin expression is a hallmark of the EMT process, which is implicated in tumor invasion, migration and metastasis.…”
Section: Discussionmentioning
confidence: 99%